Self Care Management Pada Lansia Anggota Prolanis di Puskesmas Grogol - Salma Azzah Vicananda; Kartinah Kartinah (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Chronic diseases are a very serious health issue and are the biggest cause of death worldwide. The prolanis program is designed to maintain the health of individuals with chronic diseases and achieve the maximum quality of life through a health care system and a proactive approach. Self care management is a person's ability to do something independently in maintaining their quality of life. The elderly experience a decrease in physical ability and lack of knowledge about self-care management, which results in self-care management behavior in elderly prolanis members to be less effective. This study aims to understand how self-care management in the elderly who are members of prolanis at the Grogol Health Center. This study was conducted with a quantitative descriptive approach, using questionnaires. The Non Random Sampling (Non Probability) technique was used in this study, using the accidental sampling technique, namely elderly prolanis members who suffer from hypertension and diabetes with a total sample of 81 respondents. The analysis used was a frequency distribution test to obtain an overview of the characteristics of respondents and the results of self-care management from elderly prolanis members at the Grogol Health Center. The results of the characteristics in this study showed that the majority of the female gender was 58 respondents (93.5%). The majority of respondents were in retired jobs as many as 46 respondents (93.9%). The last education of the majority was in the undergraduate category with 41 respondents (97.6%). The majority of the elderly have a history of hypertension with 40 respondents (95.2%). This study shows that the results of self-care in the elderly members of prolanis are in the good category as many as 76 respondents (93.8%). The proposal for further research is to examine other variables related to self-care in the elderly. Keywords: Self Care Management, Elderly, Prolanis, Chronic Disease. ABSTRAK Penyakit kronis adalah isu kesehatan yang sangat serius dan merupakan penyebab terbesar kematian di seluruh dunia. Program prolanis dirancang untuk menjaga kesehatan individu dengan penyakit kronis serta mencapai kualitas hidup yang maksimal melalui sistem pelayanan kesehatan dan pendekatan yang proaktif. Self care management adalah kemampuan seseorang untuk melakukan sesuatu secara mandiri dalam menjaga kualitas hidupnya. Para lansia mengalami penurunan kemampuan fisik dan kurangnya pengetahuan mengenai self care management, yang mengakibatkan perilaku self care management pada lansia anggota prolanis menjadi kurang efektif. Penelitian ini bertujuan untuk memahami bagaimana self care management pada lansia yang tergabung dalam prolanis di Puskesmas Grogol. Studi ini dilakukan dengan pendekatan deskriptif kuantitatif, dengan menggunakan kuesioner.Teknik Non Random Sampling (Non Probability) digunakan dalam penelitian ini, dengan menggunakan teknik accidental sampling yaitu lansia anggota prolanis yang menderita hipertensi dan diabetes dengan total sampel sebanyak 81 responden. Analisis yang digunakan adalah uji distribusi frekuensi memperoleh gambaran tentang karakteristik responden serta hasil self care management dari lansia anggota prolanis di Puskesmas Grogol. Hasil karakteristik pada penelitian ini menunjukkan mayoritas pada jenis kelamin perempuan sebanyak 58 responden (93,5%). Mayoritas responden yaitu pada pekerjaan pensiunan sebanyak 46 responden (93,9%). Pendidikan terakhir mayoritas adalah pada kategori sarjana dengan 41 responden (97,6%). Lansia mayoritas memiliki riwayat penyakit hipertensi dengan 40 responden (95,2%). Penelitian ini menunjukkan hasil bahwa self care pada lansia anggota prolanis yaitu pada kategori baik sebanyak 76 responden (93,8% ). Usulan bagi riset selanjutnya yaitu untuk meneliti variabel lain yang berhubungan dengan self care pada lansia. Kata Kunci: Self Care Management, Lansia, Prolanis, Penyakit Kronis.